An n-valued neutrosophic set method for the assessment of an offshore oil spill risk. (21st March 2023) - Han, Minglei; Fan, Changxing; Huang, Shan; Hu, Keli; Fan, En
Abstract: With the development of maritime transportation, oil spill accidents occur frequently. In this paper, a scientific and reasonable assessment of ship oil spills, offshore oil platform oil spills, and subsea pipeline oil spills is carried out, and a risk assessment method of an offshore oil spill based on an n -value neutrosophic set is proposed. First, the oil spill risk evaluation index systems of these three risk sources are constructed, respectively, and the entropy weight method is used to calculate the weight. Second, we establish a risk assessment model under the n -value neutrosophic environment. Furthermore, we use the n -value neutrosophic-weighted arithmetic average (NVNWAA) to calculate the risk levels of the following three risk sources: ship oil spills, offshore oil platform spills, and submarine pipeline spills. Finally, according to the results of the risk assessment, the countermeasures to strengthen the preventive measures of oil spill accidents are put forward. HIGHLIGHTS: Establish risk assessment index systems for oil spills on ships, offshore oil platforms, and undersea pipelines. Propose an n -value neutrosophic-weighted arithmetic average operator. Propose the entropy weight method to calculate the weight of indexes. Develop an oil spill risk assessment model based on an n -value neutrosophic. Discuss the prevention measures related to an oil spill of three risk sources. Graphical Abstract